2019
DOI: 10.1155/2019/7670316
|View full text |Cite
|
Sign up to set email alerts
|

Histone Arginine Methylation-Mediated Epigenetic Regulation of Discoidin Domain Receptor 2 Controls the Senescence of Human Bone Marrow Mesenchymal Stem Cells

Abstract: The application of human bone marrow mesenchymal stem cells (hBM-MSCs) in cell-based clinical therapies is hindered by the limited number of cells remaining after the initial isolation process and by cellular senescence following in vitro expansion. Understanding the process of in vitro senescence in hBM-MSCs would enable the development of strategies to maintain their vitality after cell culture. Herein, we compared the gene expression profiles of human embryonic stem cells and human BM-MSCs from donors of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Therefore, it is not surprising to observe that DDR2 is also required for proper neuroblastoma cell proliferation. Furthermore, recent work from Xu et al (48) suggested that epigenetic downregulation of DDR2 in human-derived bone marrow mesenchymal stem cells is associated with reduced proliferation and increased senescence of these cells, which is in agreement with our findings in SH-SY5Y neuroblastoma cells. Importantly, a previous work demonstrates that pharmacologic inhibitions or genetic ablation of DDR2 in several neuroblastoma cell lines impairs their proliferation and in vivo tumor growth and metastasis (Rozen et al, 2023 under revision).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is not surprising to observe that DDR2 is also required for proper neuroblastoma cell proliferation. Furthermore, recent work from Xu et al (48) suggested that epigenetic downregulation of DDR2 in human-derived bone marrow mesenchymal stem cells is associated with reduced proliferation and increased senescence of these cells, which is in agreement with our findings in SH-SY5Y neuroblastoma cells. Importantly, a previous work demonstrates that pharmacologic inhibitions or genetic ablation of DDR2 in several neuroblastoma cell lines impairs their proliferation and in vivo tumor growth and metastasis (Rozen et al, 2023 under revision).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with our findings that DDR2 is also required for proper neuroblastoma cell proliferation. Furthermore, a recent study from Xu et al [57] suggested that epigenetic downregulation of DDR2 in human-derived bone marrow mesenchymal stem cells is associated with reduced proliferation and increased senescence of these cells, which is in agreement with our findings in SH-SY5Y neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…DNA damage progressively accumulates with cell aging increasing the risk of genomic instability [2]. Accordingly, in vitro aged BM-MSCs display increased γH2AX [136]. In general, MSC phenotype is stable in culture [17,26,137]; conventional surface markers seem not modified during in vitro aging, whereas Stro-1 (stromal cell surface marker-1), CD106 (VCAM-1) and CD146 (MCAM) appear downregulated during prolonged culture [2,29].…”
Section: In Vitro Msc Senescencementioning
confidence: 99%
“…The discoidin domain receptor 2 (DDR2, a tyrosine kinase collagen receptor expressed by MSCs) was found to be correlated with in vitro BM-MSC senescence: it plays a relevant role in BM-MSC commitment towards osteogenic differentiation rather than adipogenic; it progressively decreases with culture passages; its inhibition in low-passage BM-MSC recapitulates senescence features. DDR2 plays therefore a major role in regulating the in vitro senescence of human BM-MSCs [136]. Moreover, coactivator-associated arginine methyltransferase1 (CARM1) was found to be the upstream up-regulator of DDR2 expression via increased H3 methylation, thus contributing to rejuvenation of late passage BM-MSCs [136].…”
Section: Epigenetics: In Vitro Datamentioning
confidence: 99%
See 1 more Smart Citation